Warmer Pliocene Upwelling Site SST Leads to Wetter Subtropical Coastal Areas: A Positive Feedback on SST. Issue 2 (27th January 2022) - Fu, Minmin; Cane, Mark A.; Molnar, Peter; Tziperman, Eli
Abstract: The early‐to mid‐Pliocene (5.3–3 Ma), characterized by warmer temperatures and similar CO2 concentrations to present day, is considered a useful analog for future warming scenarios. Geological evidence suggests that during the Pliocene, many modern‐day desert regions received higher levels of rainfall and supported large perennial lakes and wetter vegetation types. These wetter conditions have been difficult to reconcile with model predictions of 21st century drying over most subtropical land regions. Using an atmospheric General Circulation Model, we show that underestimates of Pliocene rainfall over certain areas in models may be related to insufficient sea surface temperature (SST) warmth simulated over relatively local eastern boundary current regions. When SSTs off the coast of California are raised to more closely match some proxy reconstructions, rainfall increases over much of adjacent western North America. Over the southwestern USA, this increased rainfall is mainly due to a convergent monsoonal circulation that develops over late boreal summer. A smaller wintertime increase in precipitation also occurs due to differences in rainfall associated with midlatitude cyclones. Wetter land conditions are expected to weaken upwelling‐favorable coastal winds, so that increased rainfall caused by coastal SST warming suggests a positive feedback that could help sustain wet, Pliocene‐like conditions. Key Points: Warm Pliocene sea surface temperatures (SSTs) at midlatitude coastal upwelling sites are a common feature of proxy reconstructions Prescribing higher SSTs along the California coast in an atmospheric model increases rainfall over western North America Precipitation differences are caused by increased mean convergence during the boreal summer and enhanced eddy fluxes in the winter